Epilepsy and Crime - Historical study and forensic - Lastres, Juan B. (1954)
Epilepsy is as old as mankind. Its history begins with the appearance of man on earth, when he suffered trauma and emotions in your body and in your soul; when the skull, brain case nonexistent, was confused and sometime later appeared framáticas seizures in members.